PREVENTIVE MEASURES TO MITIGATE THE RISK OF FRAUD IN LETTERS OF CREDIT TRANSACTIONS IN MALAYSIA (UUM Journal of Legal Studies, 2021)
This article attempts to analyse the issue of fraud in letters of credit (LC) transactions, also known as documentary credits. There are numerous reported cases of fraud in LC transactions, which remain a continuing risk. The UCP 600 is a popular standard of practice for banks, which confirms that banks must honour payment to the seller upon full compliance with the documentary credit requirements. Such payments have been made despite being presented with falsified documents or substandard goods being delivered. It might not be realistic to expect that the International Chamber of Commerce (ICC) can create global standards relating documentary credits, which cover the practicalities of the existing system and relevant legalities applicable to the letter of credit system in international trading. Each party involved may have a responsibility to take some preventive measures to mitigate the risk of fraud. The doctrinal method is used to conduct this study because it involves an in-depth analysis of the gap within the Malaysian system and the strategies that maybe be adopted to overcome the risks associated with LC fraud. Findings reveal that LC documents can be easily falsified, and the occurrence of LC fraud is not uncommon in Malaysia. However, given the lack of literature it has not been highlighted in the past couple of years. The primary focus of this article is to suggest preventive measures that the respective parties could take to protect themselves from fraudulent dealings involving LCs.